PENGARUH PROFITABILITAS, LEVERAGE, DAN REPUTASI UNDERWRITER TERHADAP UNDERPRICING SAHAM INITIAL PUBLIC OFFERING (IPO) DI BEI PERIODE 2022–2025 - Nurul Amelia Putri; I Gusti Ketut Agung Ulupui; Eka Septariana Puspa (CV. Denasya Smart Publisher, 2026)
The underpricing condition observed during Initial Public Offerings (IPOs) has attracted considerable attention as it reflects the discrepancy between the IPO offering price and the stock's market price on the first trading day, which may influence investment decisions and companies' fundraising strategies. which may influence investment decisions and companies’ fundraising strategies. This research seeks to investigate the effect of profitability, financial leverage, and underwriter reputation on IPO underpricing rates among firms listed on the Indonesia Stock Exchange during the 2022–2025 period. This study adopts a quantitative research method with a causal approach and utilizes multiple linear regression techniques to analyze the relationship between variables. The research relies on secondary data collected where the research sample was obtained through the application of a purposive sampling technique, resulting in a final sample of 142 companies that fulfilled the predetermined research criteria. The findings show that profitability has a positive and statistically significant impact on underpricing, while financial leverage has no significant effect on underpricing. Meanwhile, underpricing is negatively and significantly affected by underwriter reputation. These findings suggest that companies’ financial conditions and the quality of underwriters play an important role in explaining IPO underpricing and may serve as considerations for investors and companies in making decisions related to initial stock offerings